Development of interventions to improve the quality of life of children and their families. - Ferreira, Cristiane Martins; Faria, Maria Eduarda Vilela; Rodrigues, Janaina Damascena; Silva, Ana Paula Arruda e; Godoy, Yasmim Albernaz Maia de; Oliveira, Jubiele Fernandes de; Rizzi, Leonardo Nunes Estrada; Santos, Franklin (Brazilian Journal of Implantology and Health Sciences, 2025)
Introduction: The presence of a chronic condition in childhood represented a multifaceted challenge that transcended the purely clinical aspects of the disease. Diagnosis and ongoing management imposed a substantial burden not only on the child, who dealt with symptoms and treatments, but on the entire family structure. Families often faced emotional stress, financial difficulties, disruption of daily routines, and an overload of caregiving functions. In this context, the quality of life of the child and that of their family members were shown to be intrinsically connected, evidencing that the well-being of the patient depended on a resilient and functional family system. Objective: The objective of this systematic review was to analyze the effectiveness of different modalities of non-pharmacological interventions aimed at improving the quality of life of children and adolescents with chronic health conditions and, simultaneously, of their respective families or primary caregivers. Methodology: A systematic review of the literature was conducted in accordance with the PRISMA guidelines, covering articles published in the last ten years. The search was performed in the PubMed, Scielo and Web of Science databases, using the following descriptors: "quality of life", "child", "chronic disease", "family" and "intervention". The inclusion criteria were: randomized clinical trials that evaluated a psychosocial or educational intervention, studies with samples of children and adolescents (0-18 years) diagnosed with a chronic condition and that measured quality of life as one of the outcomes. Observational studies, review articles and research focused exclusively on pharmacological interventions were excluded. Results: The results found in the literature indicated that the most effective interventions were those of a multicomponent nature and focused on the family. Psychoeducational programs for parents, which aimed to improve disease management skills and coping strategies, demonstrated a significant positive impact on family quality of life and on reducing parental stress. For children, interventions based on cognitive-behavioral therapy (CBT) were shown to be effective in reducing anxiety and depression associated with the disease. Family-centered care models that promoted communication and shared decision-making were also consistently associated with better outcomes for the child-family dyad. Conclusion: The development of interventions to improve the quality of life of children with chronic illnesses and their families was most successful when adopting a biopsychosocial and systemic approach. The most promising strategies were those that transcended the treatment of the child’s symptoms and focused on empowering and supporting the entire family unit. The evidence reinforced that strengthening parental resilience and improving family dynamics were essential components to promote well-being and quality of life for all involved.